Analisis kesalahan penggunaan tanda baca dan huruf miring dalam teks berita online detiknews dan tribunnews - Anisa Yuli Rahma Fitriani; Laili Etika Rahmawati (Universitas Ahmad Dahlan, 2020)
This study aims to (1) describe the form of language errors in terms of the use of punctuation and italics contained in the online news text detik news and news stands, (2) Explain the form of language errors in terms of the use of punctuation and dominant italics appear in online news text seconds news and news stands. This research uses descriptive research with a qualitative approach. The data in this research are sentences containing language errors in punctuation in online news text detik news and news stands. Data collection techniques used are reading and note-taking techniques. reading techniques, namely by reading repeatedly the contents contained in the online news column. Next, note-taking techniques are used to write down problems in reading. The note taking technique used is to write down words or sentences which are forms of spelling mistakes in the language. After being analyzed and described based on the form of errors in the spelling fields which include punctuation and italics, then it is concluded from the improvement of the sentence. The results showed that the analysis of spelling errors in the form of punctuation and italics contained 11 errors from two online news detiknews and tribunnews.